Sell more with sales coaching : practical solutions for your everyday sales challenges - Shawn, Peri (Wiley, 2013)
BSales coaching strategies to help you sell more/b Corporate sales executives are looking for ways to increase their revenues without major changes to their technology, processes, or workforce management. By implementing the Coaching and Sales Institute's coaching strategies to improve their sales conversations, some corporations have been able to as much as double their sales results. The sales coaching philosophy, tools, and exercises shared in iSell More with Sales Coaching/i are based on more than twenty-five years of research, development, and practical application in the corporate world. An assessment enables a team leader to identify which of the top ten sales mistakes are being committed by their teams. As a result of applying the tools and strategies in this book, sales leaders and teams will drive higher revenues and performance by assessing and determining what coaching is required, identifying sales mistakes being committed by team members, and coaching team members to demonstrate more effective sales behaviors.ulliHelps sales people improve the quality of sales conversations/liliHelps sales managers improve the quality of conversations within the team/liliThe author's company has worked with large sales forces and provided training for the launch of the debit card, the Blackberry, and one of the fastest-growing divisions of the Royal Bank of Canada/li/ul iSell More With Sales Coaching/i will help your team improve the quality of their communication and persuasion skills and raise your revenues.